Impact of Electrode Type on Mapping of Scar‐Related VT. (10th September 2015) - BERTE, BENJAMIN; RELAN, JATIN; SACHER, FREDERIC; PILLOIS, XAVIER; APPETITI, ANTHONY; YAMASHITA, SEIGO; MAHIDA, SAAGAR; CASASSUS, FREDERIC; HOOKS, DARREN; SELLAL, JEAN‐MARC; AMRAOUI, SANA; DENIS, ARNAUD; et al.
Mapping of Scar‐Related VT: Background: Substrate‐based VT ablation is mostly based on maps acquired with ablation catheters. We hypothesized that multipolar mapping catheters are more effective for identification of scar and local abnormal ventricular activity (LAVA). Methods and results: Phase1 : In a sheep infarction model (2 months postinfarction), substrate mapping and LAVA tagging (CARTO ® 3) was performed, using a Navistar (NAV) versus a PentaRay (PR) catheter (Biosense Webster). Phase2 : Consecutive VT ablation patients from a single center underwent NAV versus PR mapping. Point pairs were defined as a PR and a NAV point located within a 3D‐distance of ≤3 mm. Agreement was defined as both points in a pair being manually tagged as normal or LAVA. Four sheep (4 years, 50 ± 4.8 kg) and 9 patients were included (53 ± 14 years, 8 male, 6 ischemic cardiomyopathy). Mapping density was higher within the scar with PR versus NAV (3.2 vs. 0.7 points/cm 2, P = 0.001) with larger bipolar scar area (68 ± 55 cm 2 vs. 58 ± 48 cm 2, P = 0.001). In total, 818 point pairs were analyzed. Using PR, far‐field voltages were smaller (PR vs. NAV; bipolar: 1.43 ± 1.84 mV vs. 1.64 ± 2.04 mV, P = 0.001; unipolar; 4.28 ± 3.02 mV vs. 4.59 ± 3.67 mV, P < 0.001). More LAVA were also detected with PR (PR vs. NAV; 126 ± 113 vs. 36 ± 29, P = 0.001). When agreement on LAVA was reached (overall: 72%; both LAVA, 40%; both normal, 82%) higher LAVA voltages were recorded on PR (0.48 ± 0.33 mV vs. 0.31 ± 0.21 mV, P = 0.0001). Conclusion: Multipolar mapping catheters with small electrodes provide more accurate and higher density maps, with a higher sensitivity to near‐field signals. Agreement between PR and NAV is low.